2023
DOI: 10.1002/eap.2903
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic differentiation and phenotypic plasticity of Ambrosiaartemisiifolia under different nitrogen levels

Abstract: Rapid adaptive evolution and phenotypic plasticity are two mechanisms that are often thought to underlie invasiveness of alien plant species, but whether they can co‐occur within invasive plant populations under altered environmental conditions such as nitrogen (N) enrichment has seldom been explored. Latitudinal clines in plant trait responses to variation in environmental factors may provide evidence of local adaptation. Here, we inferred the relative contributions of phenotypic plasticity and local adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…For some exotic plant species, both local adaptation and phenotypic plasticity may jointly facilitate invasion. For instance, both local adaptation and phenotypic plasticity were linked to successful invasion by Wedelia trilobata (Asteraceae) (Si et al, 2014 ), A. artemisiifolia (Xiong et al, 2023 ), and Prunella vulgaris (Lamiaceae) (Godoy et al, 2010 ). It is likely that phenotypic plasticity and local adaptation both underlie the invasiveness of S. canadensis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some exotic plant species, both local adaptation and phenotypic plasticity may jointly facilitate invasion. For instance, both local adaptation and phenotypic plasticity were linked to successful invasion by Wedelia trilobata (Asteraceae) (Si et al, 2014 ), A. artemisiifolia (Xiong et al, 2023 ), and Prunella vulgaris (Lamiaceae) (Godoy et al, 2010 ). It is likely that phenotypic plasticity and local adaptation both underlie the invasiveness of S. canadensis .…”
Section: Discussionmentioning
confidence: 99%
“…For some exotic plant species, both local adaptation and phenotypic plasticity may jointly facilitate invasion. For instance, both local adaptation and phenotypic plasticity were linked to successful invasion by Wedelia trilobata (Asteraceae) (Si et al, 2014), A. artemisiifolia (Xiong et al, 2023),…”
Section: Q St -F St Comparisons Suggest That Directional and Stabiliz...mentioning
confidence: 99%
“…While local adaptation and phenotypic plasticity in functional traits are potential influencers of the invasiveness of alien plants, their relative contributions remain uncertain. According to Xiong et al (2023), adaptive evolution and phenotypic plasticity in various traits may work in synergy to enhance the invasiveness of Ambrosia artemisiifolia in China under varying nitrogen levels. Their results showed that both phenotypic plasticity and rapid adaptive evolution could enable invasive plants to thrive across diverse environmental conditions.…”
Section: Mechanisms Of Invasion Successmentioning
confidence: 99%